The Effect of Oral Contraceptive Pills on The Gene Mutation of Factor V Leiden among Sudanese Women - Kawthar Abdelgaleil Mohammed Salih; Hiba Abdelmalik; Hiba Babiker; Ahmed Bakheet Abd Alla (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2020)
Oral contraceptive pills are problems for women, often have many effects, and may cause several diseases. The purpose of this research was to determine the impact of oral contraceptive pills on factor V sufferers. This case-control study conducted in Khartoum Sudan during the period from April to November 2018. The study included 50 women who used oral contraceptive as a case and 50 women who did not use oral contraceptive pills as a control, all of whom were verbally informed of the study and approved for participation. The PCR do for each sample. The results obtained from cases show that the mean age is 30±5.5 and divided into three groups less than 20 with a lower frequency of 4 % (2/50), (20-35) with a higher incidence of 80 % (40/50) and a higher rate of 16 % (8/50) for more than 35 years. Most cases use the oral contraceptive pill for more than one year at a frequency of 60% (30/50) with a mean of 2±0.8. The most frequent oral contraceptive pill use was levonorgestrel 88% (44/50), followed by desogestrel 12% (6/50). The study concludes that there is no significant difference in gene mutation between case and control. There was also an insignificant association between the mutation and demographic data.